Integrating Olfaction in a Robotic Telepresence Loop - González-Monroy, Javier; Meléndez-Fernández, Francisco; Góngora González, Andrés; González-Jiménez, Antonio Javier (IEEE, 2017)
In this work we propose enhancing a typical robotic telepresence architecture by considering olfactory and wind flow information in addition to the common audio and video channels. The objective is to expand the range of applications where robotics telepresence can be applied, including those related to the detection of volatile chemical substances (e.g. land-mine detection, explosive deactivation, operations in noxious environments, etc.). Concretely, we analyze how the sense of smell can be integrated in the telepresence loop, covering the digitization of the gases and wind flow present in the remote environment, the transmission through the communication network, and their display at the user location. Experiments under different environmental conditions are presented to validate the proposed telepresence system when localizing a gas emission leak at the remote environment.
Keywords: Robots autónomos; Robotic telepresence; Artificial olfaction; Mobile robot